Palms of riverine communities as a sustainable resource in the Brazilian Amazon - de Andrade Miranda, Ires Paula (2008)
In the Amazon, approximately 30% of the population is agglomerated in small villages or isolated areas. One of the most serious problems is the lack of electricity, where reduced supply and frequent rationing reduce life quality and prevent the instalation of industries that could raise the value of renewable regional products. Consequently, the pursuit of better socioeconomic conditions promote the quick depletion of natural resources, which invariably results in the accelerated destruction of local ecosystems. Oil palms, that are mainly used for basic nutrition of local populations, could also form the basis for models of self-sustained technological and industrial development. A quantitative survey of native species of oil palms offers an alternative for sustained development based on a technological and industrial model because this resource occurs in populated areas in the Amazon, which facilitates retaining the people in the field, preventing the depletion of natural ecosystems. This study presents the activities that were used to identify the potential of biomass of Euterpe precatoriaMart and other oil palms available in riverside communities in the state of Amazonas (Brazil). These activities are associated with the possibilities of using palm species for sustainable development of energy generation. It was possible to identify the conditions for a sustainable supply of biomass as an alternative energy source which contributes to the Energy Universalization Program in the Brazilian Amazon.